An IoT-Based Approach to an Intelligent Irrigation System (International Journal of Innovative Research in Computer Science & Technology, 2021)
The technology (IOT) is a huge influx of  technological advancements (ICT). The Iot technology  (IoT) is a broad phrase that encompasses a wide range of  capabilities, possible uses, multiple data collection, and  operating approaches. The present IOT research activities  are centered on the creation but also design of mandates  and open infrastructures, which still have issues that must  be overcome before they can be fully implemented. This  paper includes an introduction of IoT technology and its  uses in farming systems, as well as a measurement of  prior survey research and a suggestion for an irrigation  management monitoring system. This project's main  purpose is to create new agricultural technologies that  will boost vegetative growth and water resources.  Following the measurement of temperature, humidity,  and moisture content, a smart control system is provided,  which employs cutting-edge electrical tech and a  microcontroller to switch the hydrostatic gear ON and  OFF when the atmosphere's most content is recognized.  Following the temperature measurements, moisture  levels, and soil moisture, a Bluetooth service member is  also offered.
Keywords: Internet of Things; Temperature; Humidity; Irrigation System; Arduino Mega